Improve The Quality of The Teacher Profession by Organizing The Teachers' Union in The Republic of Indonesia (PGRI) - Christin Nur Aini; Lailatul Mukarromah; Puji Rahayu (Lembaga Junal dan Publikasi, Universitas Muhammadiyah Buton, 2022)
The current state of education presents a problem for teachers. Therefore, educators must improve their quality in line with the times. In the field of education, a teacher's professionalism is crucial. Because pupils can develop themselves to their fullest potential with the help of experienced teachers. Therefore, raising the standard of the teaching profession is thought to be crucial. Additionally, educating, teaching, guiding, directing, training, and evaluating students is a teacher's primary responsibility. The professionalism of a teacher has a direct impact on the quality of the teacher. For pupils to be able to think critically and creatively, teachers must be able to act as facilitators. Teachers must also have the ability to act as a spark for pupils to pursue their interests and skills.